2007
DOI: 10.1159/000099194
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ion Transport in Mouse Proximal and Distal Colon by Prolactin

Abstract: The lactogenic hormone prolactin (PRL) has been known to affect Ca2+ and electrolyte transport in the intestinal epithelium. In the present study we analyzed ion transport in mouse proximal and distal colon, and acute changes induced by PRL. In the proximal colon, carbachol activated a Ca2+ dependent Cl- secretion that was sensitive to DIDS and NFA. In the distal colon, both ATP and carbachol activated K+ secretion. Ca2+ -activated KCl transport in proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
2
24
2
Order By: Relevance
“…Moreover, cAMP-and Ca 2+ -activated currents were similar in wt and APC Min/+ , and the effects of paxillin, astemizole, or 4-AP could not be detected (data not shown). Thus, Ca 2+ -activated BK channels and astemizole-sensitive Eag-1 channels are most likely expressed in the surface epithelium, which confirms previous results [24]. RPD due to activation of BK K + channels.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, cAMP-and Ca 2+ -activated currents were similar in wt and APC Min/+ , and the effects of paxillin, astemizole, or 4-AP could not be detected (data not shown). Thus, Ca 2+ -activated BK channels and astemizole-sensitive Eag-1 channels are most likely expressed in the surface epithelium, which confirms previous results [24]. RPD due to activation of BK K + channels.…”
Section: Resultssupporting
confidence: 90%
“…However, Akt may also increase the activity of Ca 2+ -activated K + cannels, since membrane trafficking of BK channels was shown to be enhanced by Akt in a PI3-kinase-dependent manner in neurons [6]. PI3-kinase-dependent regulation of BK was also found in mouse distal colon [24]. BK β1 and BK β2 subunits were largely increased in the distal colon of APC Min/+ animals (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…However, previous work suggested that also Ano10 is able to produce Ca 2+ -activated Cl − currents [43,49,51]. The present data indicate expression of a number of anoctamin paralogues in mouse intestine, with Ano1 and Role of Ano1 for intestinal Cl − secretion Ca 2+ -dependent Cl − secretion was detected in rat and mouse naïve colonic epithelium, in contrast to the human large intestine, which does not express anoctamin 1 [18,24,29,40]. It is noteworthy that analysis of anoctamin expression and Ca 2+ -dependent transport should take place in naïve intestinal mucosa rather than in cultured epithelial cells, since cultured cells behave differently, even when grown under polarized conditions [24].…”
Section: Discussioncontrasting
confidence: 40%
“…When stimulated by secretagogues such as ATP and carbachol that increase the intracellular Ca 2ϩ concentration, predominantly K ϩ channels are activated, hyperpolarizing the membrane voltage. This is comparable with colonic crypt cells, which also activate Ca 2ϩ -activated K ϩ channels upon stimulation of basolateral muscarinic M3 and apical purinergic P2Y 2 receptors (18,19). In contrast, T 84 cells that had undergone spontaneous transformation were remarkably different: they proliferated much faster, were unable to polarize or form tight monolayers when grown on permeable supports, showed typical features of malignancy, and had different membrane conductances.…”
Section: Transformation Of Colonic Epithelial Cells Increases Prolifementioning
confidence: 54%